Geospatial Modeling To Assess Geomorphological Risk For Relentless Shifting Cultivation In Garo Hills Of Meghalaya, North East India - Yadav, Pramod Kumar; Sarma, Kiranmay; Mishra, Ashish Kumar (International Journal of Environment, 2013)
Due to shifting cultivation, the overall structure and composition of ecological condition is affected, hence landscape study becomes important for maintaining ecological diversity and appropriate scientific planning of any area. Garo hills region of northeast India is suffering from Geomorphological risk like sheet erosion, landslide etc. due to the age old tradition of shifting cultivation in the fragile hill slopes aided by other anthropogenic activities. The present study was conducted to examine the role of shifting cultivation for deforestation and degradation with variant of slope and elevation to relate vegetation cover with slope and elevation in the Garo Hills landscape of Meghalaya using temporal remote sensing data of 1991, 2001 and 2010. It revealed that there is decrease in dense forest and open forest during the 1st decade while areas under dense forest and non-forest increased in 2nd decade. This increased forest area is confined in the high slopes, which are inaccessible. The study shows increase in shifting cultivation near-about double fold in high slope and more than a double fold in the high altitudinal area in last decade, which is negative sign in terms of Geomorphological protection. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 91-104 DOI: http://dx.doi.org/10.3126/ije.v2i1.9212